The Great Equity Evasion: The Society for Human Resource Management’s Discomfort with Diversity’s Fair Share, an Issue in the Workplace - Stacey L. Morin; Darrell Norman Burrell (Business Ethics and Leadership)
The Society for Human Resource Management recently decided to remove "equity" from the diversity, equity, and inclusion framework, sparking substantial debate within the human resources community. This research examines the consequences of this decision, focusing on the potential impacts on organizational practices, employee experiences, and the broader human resources field. The relevance of this research lies in the critical role equity plays in addressing systemic inequalities and ensuring fair treatment, access, and opportunities for all individuals. The primary purpose of this study is to analyze how the omission of equity from diversity, equity, and inclusion initiatives may affect effectiveness, potentially leading to superficial diversity measures, employee disillusionment, and reputational risks for organizations. The study employed a review of existing literature. The contribution to addressing the scientific problem under investigation lies in applying a theoretical framework that integrates Critical Race Theory and Organizational Justice Theory, enabling a rigorous examination of how systemic inequalities may persist or be exacerbated when equity is not explicitly prioritized within initiatives. This application demonstrates the importance of a theoretical basis for analyzing such complex issues. This approach allows for a comprehensive understanding of the implications of the Society for Human Resource Management's decision and provides insights into the necessity of maintaining a focus on equity within frameworks to promote genuine inclusivity and fairness in the workplace.